Analisa Faktor Yang Mempengaruhi Waktu Tunggu Pelayanan Obat Pasien Rawat Jalan Di Instalasi Farmasi Rumah Sakit Dr. Oen Kandang Sapi Solo - Rara Elyza Herasmara Triagypta; Muljadi Hartono; Warsini; Lilik Sriwiyati (Journal of Innovative and Creativity, 2025)
Background: With advancements in medical technology, hospitals can provide fast and accurate medical services, serving as referral hospitals according to their level. The waiting time for prescription services also affects patients' expectations of hospital services, particularly pharmaceutical services. Efforts to reduce waiting times are necessary to enhance patient satisfaction, treatment effectiveness, and the workload of medical staff. Objective: The aim of this study is to identify the factors that influence the waiting time for outpatient medication services. Method: This research employs a mixed-method approach. The population in this study consisted of 10,607 prescription sheets and 23 pharmacy staff. The sample was taken using Slovin's formula, resulting in 385 prescription sheets and 10 staff members selected through consecutive sampling. Data analysis was conducted using Chi-square tests and qualitative analysis. Results: The study found that 93.5% of prescription sheets had waiting times that complied with standard of the minister of health, while 6.5% did not. The research also revealed no significant effect between the type of prescription and the compliance of waiting times for medication services at Dr. OEN KANDANG SAPI SOLO HOSPITAL, with a p-value of 0.134 (p>0.05). However, interviews indicated that factors such as drug availability, prescription completeness, human resources availability, and the availability of facilities and equipment do influence waiting times for medication services. Conclusion: The waiting time for medication services at the Pharmacy Installation of Dr. OEN KANDANG SAPI SOLO HOSPITAL mostly meets the standards. The type of prescription does not have a statistical impact; however, factors such as drug availability, prescription completeness, human resources, and facilities and equipment can affect waiting times.